ANALISIS NERACA AIR PERTANIAN DI SUB DAS RAWATAMTU (Analysis of agricultural water balance in Rawatamtu sub-watershed) - Erwan Bagus Setiawan; Indarto Indarto; Sri Wahyuningsih (Center for Implementation of Standards for Environmental and Forestry Instruments Solo, 2019)
ABSTRACTPopulation growth, urbanization, industrial development, and agricultural activities increase water demand on the watershed. An increase in water demand will propagate the excessive exploitation of surface water and groundwater resources. This will probably influence the water balance of the watershed. Therefore, understanding the water balance is a necessity. Continuous imbalance between water supply and demand will generate many serious environmental problems. A study of agricultural water balance is needed to answer the question whether the available water resources can meet the needs of sufficient water for irrigation. The study was conducted in Rawatamtu sub-watershed which was part of Bedadung Watershed. The Water Evaluation and Planning (WEAP) model was used to analyze agricultural water balance. The procedure included inventory data, installing WEAP on the system, running the WEAP, and using WEAP for simulating future water balance conditions. The simulation results showed that agricultural water balance for the next 10 years will be more frequently in surplus condition rather than in deficit condition. The water surplus was estimated to occur in the year of 2020, 2021, 2023, 2025, 2027 and 2028. The highest surplus occurred in the year of 2028 which reached 56.59 million m3. Furthermore, the potential water balance deficit was projected to occur in 2019, 2022, 2024, and 2026.Keywords: agricultural water balance; WEAP; agricultural water needs; Rawatamtu ABSTRAKPeningkatan kebutuhan air dipicu oleh peningkatan pertumbuhan penduduk, urbanisasi, pembangunan industri, dan peningkatan kegiatan pertanian. Kebutuhan air yang meningkat ini akan menyebabkan eksploitasi yang berlebihan terhadap sumberdaya air tanah dan air permukaan. Hal ini memungkinkan akan mempengaruhi neraca air DAS. Oleh karena itu diperlukan pemahaman terhadap keseimbangan air. Ketidakseimbangan antara jumlah ketersediaan air dan kebutuhan yang berkepanjangan akan menimbulkan dampak terhadap masalah lingkungan yang serius. Kajian tentang neraca air pertanian diperlukan untuk menjawab pertanyaan apakah sumber daya air yang tersedia dapat memenuhi kebutuhan air yang cukup untuk irigasi. Studi ini dilakukan di Sub DAS Rawatamtu yang merupakan bagian dari DAS Bedadung. Model Water Evaluation and Planning (WEAP) digunakan untuk menganalisis neraca air. Prosedur ini mencakup inventarisasi data, instalasi WEAP pada sistem, menjalankan WEAP, dan pelaksanaan simulasi WEAP untuk proyeksi kondisi neraca air masa depan. Hasil simulasi menunjukkan bahwa neraca air pertanian selama 10 tahun ke depan di Sub DAS Rawatamtu akan lebih sering berada dalam kondisi surplus daripada dalam kondisi defisit. Surplus air diperkirakan terjadi pada tahun 2020, 2021, 2023, 2025, 2027, dan 2028. Surplus tertinggi terjadi pata tahun 2028 yang mencapai 56,59 juta m3. Lebih lanjut, potensi defisit neraca air diproyeksikan akan terjadi pada tahun 2019, 2022, 2024, dan 2026.Kata kunci: neraca air pertanian; WEAP; kebutuhan air pertanian; Rawatamtu